2011
DOI: 10.1177/0969733011416398
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of common arguments against Advance Directives

Abstract: Advance Directives are under-utilized, both from the fact that few Americans have them and that health professionals don't always rely on Advance Directives provided by patients. Many health professionals have philosophical objections to their use. Using a fictitious case as background, five different objections to the use of Advance Directives will be discussed and arguments against those objections will be posed along with suggestions to improve Advance Directives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 10 publications
(16 reference statements)
0
14
0
Order By: Relevance
“…A total of six clinical cases were reviewed across the 15 articles (see table 3), as seven (47%) of the articles reported the same case (case A, a well-publicised case of a 26-year-old woman who died in the UK). Two of the clinical cases presented fictional scenarios 2 22…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of six clinical cases were reviewed across the 15 articles (see table 3), as seven (47%) of the articles reported the same case (case A, a well-publicised case of a 26-year-old woman who died in the UK). Two of the clinical cases presented fictional scenarios 2 22…”
Section: Resultsmentioning
confidence: 99%
“…A reliance on judging a person’s capacity to make a decision in the context of suicidal behaviour was discussed in detail 8 22 24. The capacity assessment was discussed in relation to when the patient was involved in advance care planning and making the decision to write an advance decision to refuse treatment 8.…”
Section: Resultsmentioning
confidence: 99%
“…Of particular importance to this element is its dependence on (1) consciousness, (2) cognitive functions, and (3) psychological continuity, and (4) its association with the other elements of personhood seen on the wider canvass of a patient's specific psychosocial, spiritual, cultural, familial, clinical, and societal situation (Parfit, 1971;Mitchell, 2012). Of particular importance to this element is its dependence on (1) consciousness, (2) cognitive functions, and (3) psychological continuity, and (4) its association with the other elements of personhood seen on the wider canvass of a patient's specific psychosocial, spiritual, cultural, familial, clinical, and societal situation (Parfit, 1971;Mitchell, 2012).…”
Section: The Individual Ringmentioning
confidence: 99%
“…This includes his self-awareness, self-control, sense of time, sense of futurity, sense of the past, capacity to relate to others, concern for others, communication with others, control of existence, curiosity, change Changes in ring sizes. Full restoration after a period of unconsciousness entails redeeming these functions to their premorbid level and ensuring the presence of psychological continuity or "the same continuing consciousness" (Parfit, 1971;Fletcher, 1979;Mitchell, 2012). Diagram B shows a reduction in size of the Individual ring, due to fluctuating/reduced consciousness or cognitive ability, e.g., in delirium.…”
Section: The Individual Ringmentioning
confidence: 99%
“…The integrative review of this work included research on the descriptors "living will" and "advance directives" in English, Portuguese and Spanish at the Biblioteca Virtual em Saúde -BVS (Virtual Health Library). The initial research revealed 51 articles, 16 of which were selected 10,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] . The Latin American and Caribbean Health Sciences (Lilacs) 10 , the Scientific Electronic Library Online (SciELO) [16][17][18] , Medical Literature Analysis and Retrieval System (Medline) [19][20][21][22][23][24][25][26] , as well as Índice Bibliográfico Español en Ciencias de la Salud -Ibecs (Spanish Bibliographic Health Sciences Index) [27][28][29][30] (Table 1) database were used for the preparation of this research.…”
mentioning
confidence: 99%